(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Face is among the most vital biometric traits. When we study the face, we can gather details such as age and gender, ethnicity, expression, identity, etc. A system for gender classification uses the faces of people from an image to identify what nature of the gender (male/female) that is the individual. A gender-based approach that is successful can improve the performance of numerous other applications, including facial recognition and a sophisticated human-computer interface. This paper provides the fundamental processing steps required for gender classification based on face images. In this paper, a variety of techniques employed in different stages in gender categorization, i.e., features extraction as well as classification are presented and contrasted.